2021
DOI: 10.1016/j.jhin.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Oral antiseptics against coronavirus: in-vitro and clinical evidence

Abstract: Background Angiotensin converting enzyme II (ACE2) is the cellular receptor for SARS-CoV-2, so ACE2-expressing cells can act as target cells and are susceptible to infection. ACE2 receptors are highly expressed in the oral cavity so this may be a potential high-risk route for SARS-CoV-2 infection. Furthermore, the virus can be detected in saliva, even before COVID-19 symptoms appear, with the consequent high risk of virus transmission in asymptomatic/pre-symptomatic patients. Reducing oral viral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 65 publications
1
50
0
2
Order By: Relevance
“…On the other hand, connections between oral dysbiosis and post-viral complications have been reported, suggesting that improving oral health may reduce the risk of complications from COVID-19 (Sampson et al, 2020), thus supporting the hypothesis of a role of dysbiosis in the virus-induced disease. Toward this direction, recent studies reported that SARS-CoV-2 load can be reduced by the use of chlorhexidine mouthwashes (Yoon et al, 2020), supporting the use of antiseptics against coronavirus infection (Koch-Heier et al, 2021;Mateos Moreno et al, 2021), and clinical studies are developing accordingly (Carrouel et al, 2020) and hopefully will help to clarify this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, connections between oral dysbiosis and post-viral complications have been reported, suggesting that improving oral health may reduce the risk of complications from COVID-19 (Sampson et al, 2020), thus supporting the hypothesis of a role of dysbiosis in the virus-induced disease. Toward this direction, recent studies reported that SARS-CoV-2 load can be reduced by the use of chlorhexidine mouthwashes (Yoon et al, 2020), supporting the use of antiseptics against coronavirus infection (Koch-Heier et al, 2021;Mateos Moreno et al, 2021), and clinical studies are developing accordingly (Carrouel et al, 2020) and hopefully will help to clarify this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the use of antiviral oral antiseptics (mouthrinses) had the potential to reduce the in vitro viral load of SARS-CoV-2, but the in vivo effectiveness was still inconclusive [ 5 ]. Only in April 2021 was it suggested that there was sufficient in vitro and in vivo evidence of the effectiveness of some oral antiseptics in inactivating SARS-CoV-2 and other coronaviruses [ 6 ] (Figure 1 (Fig. 1) ).…”
Section: Letter To the Editormentioning
confidence: 99%
“…Other authors [ 3 , 7 ] have suggested the use of mouthwashes before any procedure that generates aerosols, such as dental care; however, official recommendations on the use of mouthwashes that contribute to the prevention or attenuation of COVID-19 in the population have not yet been published.…”
mentioning
confidence: 99%
“…Mouthwashes with CPC are low-cost, clinically safe and easily accessible products for the general public, with an in vitro antiviral effect superior to chlorhexidine [ 1 , 7 ]; similarly, CPC could be added to body disinfectants to decrease the amount of virus spread [ 9 ]. On the other hand, the recommendations made by governments and healthcare providers need to be based on complete and conclusive evidence, so that the use of this type of product can be massively communicated.…”
mentioning
confidence: 99%